2014
DOI: 10.1007/s00253-014-6215-4
|View full text |Cite
|
Sign up to set email alerts
|

Overview on the biotechnological production of l-DOPA

Abstract: L-DOPA (3,4-dihydroxyphenyl-L-alanine) has been widely used as a drug for Parkinson's disease caused by deficiency of the neurotransmitter dopamine. Since Monsanto developed the commercial process for L-DOPA synthesis for the first time, most of currently supplied L-DOPA has been produced by the asymmetric method, especially asymmetric hydrogenation. However, the asymmetric synthesis shows critical limitations such as a poor conversion rate and a low enantioselectivity. Accordingly, alternative biotechnologica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
72
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 90 publications
(84 citation statements)
references
References 30 publications
0
72
0
Order By: Relevance
“…In general, chemical synthesis and the enzymatic route are the most common methods employed for preparing UAAs. For example, L‐DOPA can be synthesized both chemically and enzymatically [42–45]. The chemical approach is often undesirable because it is complex and requires expensive metal catalysts, high temperatures, and harsh reaction conditions.…”
Section: Uaa Synthesis For Biosynthetic Incorporationmentioning
confidence: 99%
See 1 more Smart Citation
“…In general, chemical synthesis and the enzymatic route are the most common methods employed for preparing UAAs. For example, L‐DOPA can be synthesized both chemically and enzymatically [42–45]. The chemical approach is often undesirable because it is complex and requires expensive metal catalysts, high temperatures, and harsh reaction conditions.…”
Section: Uaa Synthesis For Biosynthetic Incorporationmentioning
confidence: 99%
“…The chemical approach is often undesirable because it is complex and requires expensive metal catalysts, high temperatures, and harsh reaction conditions. In contrast, the enzymatic approach, which requires only mild reaction conditions, can potentially produce L‐DOPA in good yields, and the resulting waste products are often biodegradable – a huge advantage when it comes to industrial applications [45]. Here we will focus on the enzymatic route because it provides an easy, inexpensive way to synthesize UAA.…”
Section: Uaa Synthesis For Biosynthetic Incorporationmentioning
confidence: 99%
“…L-DOPA is used for treating Parkinson's disease and also a precursor for synthesizing valued benzylisoquinoline alkaloids 27,28 . Various biotechnological approaches have been applied for L-DOPA production, including microbial fermentation, immobilized tyrosinase as well as electroenzymatic system 29 . Previous studies have revealed an over 3.5 mg L −1 of L-DOPA production from glucose in yeast, using a tyrosine hydroxylase developed from a cytochrome P450 L-DOPA oxidase 30,31 .…”
Section: Discussionmentioning
confidence: 99%
“…The high cost of enzymes becomes one of the disadvantages of the enzyme-based process. Current biotechnological needs are enhanced enzyme productivity and development of techniques to increase the shelf-life of enzymes for various applications [10]. These requirements are essential to facilitate large-scale and economical formulation.…”
Section: Introductionmentioning
confidence: 99%